The Cry of a Delta: A Postcolonial Eco-Critical Study of Amitav Ghosh’s Gun Island (London Journal of Research In Humanities and Social Sciences, 2025)
Extreme urbanization and industrialization have become a direct threat to the environment and the communities associated with it. By establishing historical parallels between the lives of residents of the Sundarbans and other cities across the world, Amitav Ghosh's novel Gun Island (2019) explores modern issues like climate change, migration, cultural and geographical shifts of migrants and employs myths, stories, symbolism, metaphors, and lavish narrative. This study examines Gun Island to show how humans and the environment have traditionally been linked in civilizations such as the Sundarbans, and how, when forced to migrate, this relationship and the people of the land, along with their cultures, dislocate to newer possibilities. The study also looks at how 'the past,' in the form of memories, myths, and traditions may keep a society and its residents intact even when they are in a foreign land. Furthermore, the study emphasizes the global reach of ecological crises to demonstrate how human and non-human lives are adversely impacted when a culture or a civilization collapses.
Keywords: Kenya.; professional regulation; public management; regulatory quality; socio-economic transformation; whole-of-government approach; Migration.; Culture; Gun Island; Environmental Crisis; Sundarbans; Legends.